Decadência e prescrição das contribuições sociais para a seguridade social - Maya, Daniel Lacasa (2007)
The discussion over the statute of limitations ( decadência ) and limitation period ( prescrição ) as regards the social contributions destined to finance the social security saw a new lining with the publication of Law no. 8,212/91, of July 24, 1991, whose articles 45 and 46 set forth ten (10) year terms for the Social Security to claim its credits, while the National Tax Code establishes a five (5) year term for the statute of limitations and limitation period for tax matters. This matter, widely discussed at administrative courts and before the Judiciary Branch, is the topic covered in this paper. With that purpose, and adopting strict assumptions, we shall discuss in Chapter I the importance of language and language used in law, with emphasis on the speeches of law makers and scholars. In Chapter II, we shall cover the juridical norms, establishing the four concepts with which we shall operate: norms introducing instruments, normative documents, prescriptive enunciations and juridical norms in the strict sense (meanings taken from normative texts). In Chapter III, we shall approach the dynamics of the statutory law system, taking as a starting point the operation of the sources of law, to later enter the domain of validity, enforceability, effectiveness and efficiency . We shall also cover normative incompatibilities, revocation, as well as about the criteria for overcoming normative incompatibilities, which are the hierarchical, time (or chronological) and specialty criteria. On its turn, Chapter IV shall be destined to the normative production control, where we shall indicate normative production vices and techniques to exercise such control, i.e.: control over constitutionality (including interpretation according to the Constitution and partial unconstitutionality without reduction of text), control over legality and control over non-application of law rules. In Chapter V we shall focus on the study of supplementary laws and general tax law rules. The topic shall cover the role of supplementary laws related to tax matters, notably the roles set forth by article 146 of the Constitution, and of the special role of system adjustment that it plays. Chapter VI shall be dedicated to the statute of limitations and limitation period for tax matters. We shall discuss these elements that terminate rights in view of the failure of its creditor to act during a specified term. In the tax arena, we shall explore the role of the supplementary law to set forth national rules on statute of limitations and limitation periods, also considering the possibility of establishing said terms. We shall also shed a light on the rules of the National Tax Code on the matter, particularly the statute of limitations and limitation period terms. Finally, Chapter VII shall bring the rules of articles 45 and 46 of Law no. 8,212/91. The ten-year terms for statute of limitations and limitation periods for the collection of social contributions destined to the social security shall then be submitted to the control over constitutionality, control over legality and control over the non application of juridical rules